Public and Patient Involvement in Doctoral Research During the COVID-19 Pandemic: Reflections on the Process, Challenges, Impact and Experiences From the Perspectives of Adults With Cerebral Palsy and the Doctoral Researcher - Manikandan, Manjula; Foley, Kevin; Gough, Jessica; Harrington, Sarah; Wall, Éabha; Weldon, Fiona; Ryan, Jennifer M.; Kerr, Claire; Walsh, Aisling; Fortune, Jennifer (Frontiers in Rehabilitation Sciences, 2022)
Cerebral Palsy (CP) is a lifelong condition, where people may experience complications as they age. Including the views of people with CP through Public and Patient Involvement (PPI) ensures that research into the condition is relevant and meaningful in addressing their concerns. However, there is a lack of evidence on incorporating the voices of adults with CP in the doctoral research process. Therefore, this paper aims to provide an overview of how adults with CP were involved in a doctoral research process during the pandemic. This paper describes the PPI process and its impact at various stages of the doctoral research process and reflects on the experiences using the INVOLVE Values and Principles framework. Five adults with CP were consulted throughout the doctoral research programme. The data for this paper is a combination of reflection notes, email exchanges, meeting minutes and informal discussions with the PPI team on their experiences of being involved in the PPI process. The doctoral researcher and adult reflections highlighted the value of collaboration and the positive impact on research at each stage of the doctoral research process. Although meetings were adapted due to the pandemic, the values of PPI were adhered to throughout the doctoral research. Involving adults with CP positively impacted the doctoral research process. It is recommended to consider individual access needs to ensure meetings and information are accessible for disabled adults. Our reflective findings and recommendations may help other researchers who plan to involve adults with CP in doctoral research.